Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1016/j.foodpol.2017.11.003
|View full text |Cite
|
Sign up to set email alerts
|

How the interplay between consumer motivations and values influences organic food identity and behavior

Abstract: * This version of the article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the publisher's final version AKA Version of Record.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
197
1
25

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 228 publications
(243 citation statements)
references
References 68 publications
(98 reference statements)
20
197
1
25
Order By: Relevance
“…The health consciousness and environment protection are considered the two most prominent motives in the organic food purchase; however, health motive dominates the environment motive (Magnusson, Arvola, Koivisto Hursti, Aberg, & Sjoden, 2003;Marette, Crespi, & Schiavina, 1999;Tregear et al, 1994;Wandel & Bugge, 1997). Health benefit is closely associated with individuals and family while environmental consciousness is more beneficial to the society (Hansen, Sørensen, & Eriksen, 2018;Magnusson et al, 2003;Tarkiainen & Sundqvist, 2005), therefore, individuals with health consciousness are more likely to take decisions which will improve their health (Becker, Maiman, Kirscht, Haefner, & Drachman, 1977;Prakash et al, 2018;Willer & Youssefi, 2007). Because they are aware and are more attentive to their health, they are, therefore, motivated to purchase products which are good for their health and improve their lifestyle and in doing this, they are said to adopt "healthy behaviour".…”
Section: Theore Tic Al Modelmentioning
confidence: 99%
“…The health consciousness and environment protection are considered the two most prominent motives in the organic food purchase; however, health motive dominates the environment motive (Magnusson, Arvola, Koivisto Hursti, Aberg, & Sjoden, 2003;Marette, Crespi, & Schiavina, 1999;Tregear et al, 1994;Wandel & Bugge, 1997). Health benefit is closely associated with individuals and family while environmental consciousness is more beneficial to the society (Hansen, Sørensen, & Eriksen, 2018;Magnusson et al, 2003;Tarkiainen & Sundqvist, 2005), therefore, individuals with health consciousness are more likely to take decisions which will improve their health (Becker, Maiman, Kirscht, Haefner, & Drachman, 1977;Prakash et al, 2018;Willer & Youssefi, 2007). Because they are aware and are more attentive to their health, they are, therefore, motivated to purchase products which are good for their health and improve their lifestyle and in doing this, they are said to adopt "healthy behaviour".…”
Section: Theore Tic Al Modelmentioning
confidence: 99%
“…Actually it is not possible to define precisely all the dimensions related to this offer. Scholars are still working to provide valid information on strategic aspects such as the market segmentation (Hansen et al, 2018;Peštek et al, 2018;Sultan et al, 2018), the role of awareness (Asif et al, 2018), the willingness to pay higher prices (Aschemann-Witzel, and Zielke, 2017), the country of origin (Thøgersen et al, 2017), the relationship with health concern (Apaolaza et al, 2018) or the perspectives on production (Popović et al, 2018). Analyzing the evidences from the market, increasing sales are registered.…”
Section: The Eco-label Frameworkmentioning
confidence: 99%
“…However, attitudes to production have evolved in a dialogue between producers and consumers, leading to developments in the perceptions of both parties (Lassen & Korzen, 2009). The non-sensory attributes of food products -in addition to their sensed qualities such as taste and texture -are important to organic consumers (Hjelmar, 2011;Magnusson, Arvola, Hursti, Åberg, & Sjödén, 2003); and among these non-sensory qualities personal health benefits are now considered to play the most important role in consumers' decisions to opt for organic (Hansen, Sørensen, & Eriksen, 2018;Apaolaza, Hartmann, D'Souza, & López, 2018;Rana & Paul, 2017;Honkanen, Verplanken, & Olsen, 2006). Studies have found that consumers who prefer organic food often describe both health and environmental concerns as motives behind their choice, but there is also some evidence that an expectation of health gains is the factor most likely to push consumers from a mere preference for organic products to actual purchases of them, overcoming the fact that organic produce is generally more expensive than the conventionally produced alternatives (Denver & Christensen, 2015).…”
Section: Introductionmentioning
confidence: 99%